To solve the quadratic equation \( x^2 - 22x + 1 = 15 \) by completing the square, we follow these steps:
-
First, rearrange the equation: \[ x^2 - 22x + 1 - 15 = 0 \] which simplifies to: \[ x^2 - 22x - 14 = 0 \]
-
Move the constant term to the other side: \[ x^2 - 22x = 14 \]
-
To complete the square, take half of the coefficient of \( x \) (which is -22), square it, and add it to both sides. Half of -22 is -11, and squaring -11 gives 121: \[ x^2 - 22x + 121 = 14 + 121 \] So, we have: \[ (x - 11)^2 = 135 \]
-
Next, take the square root of both sides: \[ x - 11 = \pm \sqrt{135} \]
-
Solve for \( x \): \[ x = 11 \pm \sqrt{135} \]
Thus, the solutions are: \[ x = 11 + \sqrt{135}, \quad x = 11 - \sqrt{135} \]
The final answer, matching the options provided, would be: \[ x = 11 + 3\sqrt{15}, \quad 11 - 3\sqrt{15} \]
Therefore, the correct response is: x=11+3√15, 11−3√15